DETERMINATION OF THE OPTIMAL CONDITIONS FOR THE SPECTROPHOTOMETRIC DETERMINATION OF Ni(II) IONS USING 7- BROMO-2-NITROSO-1-OXYNAPHTHALENE-3,6-DISULFOXIDE - Nazirov Sh.S; Turaev Kh.Kh (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. In this article, the spectrophotometric detection method of complexing Ni(II) ion with 7-bromo-2-nitroso-1-oxynaphthalene-3,6-disulfoacid (BNOKS-S, S- 3,6) (HR) with organic analytical reagent developed and studied optimal conditions: λ max = 640, pH = 6,5, universal buffer, reagent - buffer - Ni(II) - distilled water, BNOKS-S with 0.05% relative to T Ni 2+ =10 μg/25ml, 1.0 ml of S-3.6 reagent was found to be sufficient. The area of obedience to the Bouguer-Lambert-Behr law was determined to be 1.0-17.5 μg/25 ml. Absorption spectra were studied: sensitivity according to Sendel was 0.0011 μg/cm2, contrast ∆λ = 100 nm.